IMPLEMENTASI ASESMEN SUMATIF PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPIT INSAN KAMIL KARANGANYAR - Nabil Latifa Muti’ah Sukma; Nur Hani’ah; Ellynia Eva Kusuma Dewi; Nurul Latifatul Inayati (ADIBA : JOURNAL OF EDUCATION, 2025)
The implementation of summative assessment in Islamic Religious Education (PAI) learning at SMPIT Insan Kamil Karanganyar aims to evaluate students' understanding and skills after the learning process. This study examines the methods, instruments, and results of the assessment implemented to determine its effectiveness in improving the quality of learning. The method applied is a case study, where data is collected through observation, interviews and document analysis. The findings show that summative assessment not only acts as a tool to measure learning outcomes, but also as feedback for teachers and students for future improvement. Thus, a good implementation of summative assessment can contribute to improving students' spiritual, social and intellectual competencies at SMPIT Insan Kamil. This study recommends further development of assessment instruments to achieve more optimal results.